Downward gazing behavior after stroke can enhance postural control even in the absence of visual input - Yogev Koren; Simona Bar-Haim; Noy Goldhamer; Noy Goldhamer; Lior Shmuelof (Frontiers in Neurology)
BackgroundRecent reports have revealed that downward gazing, a common behavior among persons with stroke, enhances postural control. The mechanism underlying this phenomenon is currently unknown. In this study, we attempt to provide evidence to support the hypothesis that this effect is primarily derived from altered retinal input caused by gazing down. We also hypothesized that the effect of downward gazing on sway will be more pronounced in subjects with impaired balance control following stroke.MethodsWe quantified standing postural sway of 20 healthy participants and 20 persons with stroke who were instructed to stand as still as possible under different conditions: while gazing forward and gazing down, with their eyes open and eyes closed.ResultsBoth the horizontal gaze angle and the lack of visual input had a negative effect on participants’ ability to attenuate their body sway. Yet, the effect of gaze angle was constant regardless of the presence or absence of visual input. Also, people with stroke were more sensitive to the effect of gaze angle.DiscussionThe results of this study indicate that downward gazing enhances postural control even in the absence of visual input and do not support our main hypothesis. Nonetheless, the effect of downward gazing on postural control was greater in unstable people (persons with stroke) than that observed in healthy adults, supporting our secondary hypothesis, which might explain less stable individuals’ tendency to gaze down while walking.